PENERAPAN KUALITAS PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) DI KECAMATAN TUALANG KABUPATEN SIAK - Amzar, Amirzan; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
One service to the community is the management of the census is the responsibility of the municipality / county, which in practice starting from villages / wards as the spearhead of population registration, until every citizen registered in the administration as a citizen of Indonesia and in accordance with Law No. 24 in 2013 on amendments to Law No. 23 of 2006 on the administration of residence.This study aims to determine how the implementation of the application of the Electronic Identity Card (e-ID) in Siak, and the factors that influence the implementation of Electronic Identity Card (e-ID) in Siak. The research looked at the implementation of Electronic Identity Card application in Siak through programs, budgets and procedures, which use qualitative methods and types of data collection using document review, interviews and observation, while the data processing procedures and data analysis using descriptive qualitative.Results of the study are based on real action undertaken by DKPS Siak in accordance with Regulation No. 9 of 2011 on Guidelines for Issuance of Identity Card-Based Electronic Standard Operating Procedures and Minister of Home Affairs in order to implement the Electronic Identity Card 2011 through strategic programs that form the structure of the organization with the name of the working group District and Sub-District, socialization, implementers (SDM), the provision of facilities and infrastructure and the mobilization of the population. Furthermore, this program is made the procedure to be carried out where the start of the Village / Village in the form of mobilization or the delivery of the invitation letter, then to the District of registering themselves for recording the population, then perform queue name-calling, the operator then verify the data, taking photographs, signatures, fingerprints , iris, fingerprint verification index then further signatures to the statement of the correctness of data is concerned. Furthermore wait Electronic ID card printing process.This activity has been realized with various obstacles such as the slow distribution of the central device and only one is functioning, the damage to the device and inaccessibility most of the population due to the delay of mobile enrollment is expected to be an alternative to meet the targets to be achieved. Thus the central unpreparedness become the main obstacle, but the government hopes district recruitment program implementers should also consider the appropriate educational qualifications as Electronic Identity Card is an information system that requires special skills.Keywords: Quality of Service, the electronic ID card